DETERMINANTS OF ANXIETY IN HOSPITALIZED PRESCHOOL CHILDREN - Suraya, Citra; Aris Citra Wisuda; Tukimin bin Sansuwito; Regidor III Dioso (Citra Internasional Institute, 2025)
Hospitalization is a stressful experience for preschool children, which can trigger anxiety due to unfamiliar surroundings, medical procedures, and separation from family. Understanding the factors that influence this anxiety is important to support children's psychological well-being. This study aims to identify the determinants of anxiety in preschool children who are hospitalized at the Siti Khadijah Islamic Hospital, Palembang. Methods A quantitative descriptive study was conducted in April 2024 involving 124 preschool children who were hospitalized. Data were collected through structured questionnaires filled out by caregivers and direct observation of children's behavior. The variables studied included age, gender, previous hospitalization experience, parental presence, type of illness, and length of hospitalization. Descriptive statistical analysis and correlation were used to process the data. The results of this study found several factors to have a significant effect on anxiety levels, such as the absence of parents, no previous hospitalization experience, invasive medical procedures, and longer hospitalization length. Age and gender also played a role; girls and younger children showed higher anxiety. The presence of parents, especially mothers, helped reduce anxiety. Children with previous hospitalization experience tended to adapt more easily. The conclusion of the study found that Anxiety of preschool children who are hospitalized is influenced by various factors such as age, gender, presence of parents, previous hospitalization experience, type of action and length of treatment. Family-based care approaches and parental presence are very important in reducing anxiety and supporting children's emotional health.